An implementation on domain name system security extensions framework for the support of IPv6 environment - Mantoro, Teddy; Norhanipah, Saiful Azhar; Bidin, Ahmad Fakhrurrazi (2011)
Domain Name System Security Extensions (DNSSEC) is a suite of Internet Engineering Task Force (IETF) specifications for securing the information provided by the Domain Name System (DNS). It is a set of extensions to DNS which provide to DNS resolvers origin authentication of DNS data, authenticated denial of existence, and data integrity. The threats from the certain attack on DNS are common and although several tools or devices have been introduced, there still needs to have a better solution in overcoming the issues. The major problem in DNS are it does not offer any form of security and it is vulnerable to spoofing, man-in-the-middle and cache poisoning attacks. At the same time, there are several factors that preventing a widespread implementation of the DNSSEC, such as security testing, performance evaluation and used functionality testing. Thus, this paper will concentrate on implementing DNSSEC framework on IPv6 environment that provides origin authentication of DNS data, data integrity, and authenticated denial of existence.